The Impact of Religiosity on the Relationship between Corporate Social Responsibility (CSR) and Organizational Commitment - Kurnia Indah Sumunar; Lu'lu'ul Jannah; Anita Anita (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
Non-financial performance variables such as corporate social responsibility (CSR) receive increased attention from stakeholders. This study examines whether CSR performance affects employees of Sharia financial institutions concerning organizational commitment and whether religiosity as a moderating variable strengthens or weakens that effect. Research on the role of employee performance toward CSR practices and the impact of those performances on employee behaviour is limited, especially in developing countries. In addition, the religiosity factor is still under consideration in terms of whether it affects employee performance. Based on information gathered from questionnaires distributed to employees of Sharia financial institutions in Indonesia, this study shows that CSR performance positively affects organizational commitment, and religiosity weakens the positive influence of CSR performance on organizational commitment. Employees feel CSR practices can affect their work performance because companies with good CSR practices could create a good reputation for their organization. AbstrakVariabel kinerja non-keuangan seperti tanggung jawab sosial perusahaan (CSR) mendapat perhatian yang besar dari para pemangku kepentingan. Penelitian ini menguji apakah kinerja CSR mempengaruhi karyawan lembaga keuangan syariah terhadap komitmen organisasi dan apakah religiusitas sebagai variable moderasi memperkuat atau memperlemah efek tersebut. Penelitian tentang peran kinerja karyawan terhadap praktik CSR dan dampak sikap tersebut terhadap perilaku karyawan masih terbatas, terutama dalam konteks negara berkembang. Selain itu, faktor religiositas masih dalam pertimbangan apakah berpengaruh terhadap kinerja karyawan. Berdasarkan informasi yang dikumpulkan dari kuesioner yang dibagikan kepada karyawan lembaga keuangan syariah di Indonesia, penelitian ini menunjukkan bahwa kinerja CSR berpengaruh positif terhadap komitmen organisasi, dan religiusitas memperlemah pengaruh positif kinerja CSR terhadap komitmen organisasi. Karyawan merasa praktik CSR dapat mempengaruhi kinerja di tempat kerja karena perusahaan dengan praktik CSR yang baik dapat menciptakan reputasi yang baik bagi organisasi.